FRI0568 Toward Standardized Musculoskeletal Ultrasound (MSUS) in Paediatric Rheumatology: Age Related Msus Normal Findings. (9th June 2015) - Collado, P.; Vojinovic, J.; Nieto, J.C.; Windschall, D.; Magni Manzoni, S.; Bruyn, G.A.W.; Iagnocco, A.; D'Agostino, M.A.; Naredo, E.
Abstract : Objectives: The OMERACT Ultrasound Task Force recently produced MSUS standard definitions of normal joint findings in healthy children. (1) Since joints anatomy changes during childhood, the group decided to collect normal joint images according to different age groups, in order to produce a reference atlas for future MSUS studies in paediatric arthritis. Methods: Prospective multicentre study: four experts in paediatric MSUS independently collected representative images of four joints (knee, ankle, wrist and second metacarpophalangeal) in 4 different predefined age groups. Experts used their own B-mode and Doppler settings for getting the best quality image and the highest sensitivity for low blood flow, and predefined scanning procedures. All images were evaluated for quality parameters as follow: image clearly fulfil the validated B-mode and Doppler US definitions and display the agreed scanning landmarks. In order to insure the reliability across machines an expert performed the same examinations using 2 different US machines. Results: Sixty-four healthy children were scanned. The quality of images was consistent across examiners. According to the age MSUS showed clearly age-related variations of joint morphology and vascularization, the latter more frequently detected within the epiphyseal cartilage at earlier age (Figure 1 ). Depending on the degree of ossification of the epiphyseal cartilage, it is showed as anechoic/hypoechoic structure which thickness was decreasing as the child was getting older. Whereas the US appearance of tendons and ligaments was the same in all age groups. There was high to good level of consistency of images quality between the two different US machines (GE Logic E9 vs GE Logic e). Conclusions: We provided a reference atlas of normal images according to the age, and created baseline knowledge of normal morphology, including blood vessels in the four joints examined. This atlas will help to differentiate normal from abnormal findings in paediatric MSUS. References: Roth J, Jousse-Joulin S, Magni-Manzoni S, Rodriguez A, Tzaribachev N, Iagnocco A, Naredo E, D'Agostino MA, Collado P and the OMERACT Ultrasound Group. Definitions for the sonographic features of joints in healthy children. Arthritis Care Res 2014; DOI: 10.1002/acr.22410 Disclosure of Interest: None declared